2020
DOI: 10.14314/polimery.2020.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Plasma deposition of antimicrobial coatings based on silver and copper on polypropylene

Abstract: This paper addresses the issue of plasma treatment of the surface of polypropylene (PP) using sputtering of silver (Ag) and copper (Cu) and their oxides with MS-PVD in order to impart antimicrobial activity. It was found that plasma treatment of PP with Cu and Ag based layers allows to provide excellent antimicrobial properties due to a constant release of metal ions. The samples of PP treated with Cu and CuO were characterized by highest antimicrobial properties and stability of the coatings. The most stable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…These radicals can damage the cell membrane leading to leakage of cytoplasm and cell death [28]. In turn, Woskowicz et al showed that the strong bactericidal properties of the AgO coated by magnetron sputtering on polymer surface can be associated with low durability of the coating and the release of ions into the environment [22].…”
Section: Antibacterial Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…These radicals can damage the cell membrane leading to leakage of cytoplasm and cell death [28]. In turn, Woskowicz et al showed that the strong bactericidal properties of the AgO coated by magnetron sputtering on polymer surface can be associated with low durability of the coating and the release of ions into the environment [22].…”
Section: Antibacterial Propertiesmentioning
confidence: 99%
“…the strong bactericidal properties of the AgO coated by magnetron sputtering on polymer surface can be associated with low durability of the coating and the release of ions into the environment [22].…”
Section: Photocatalytic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Good antimicrobial activity against Gram-negative and Gram-positive test bacteria with clinical significance was found by Stoyanova et al [43] for RF magnetron co-sputtered Ag and Cu doped TiO 2 coatings. Woskowicz et al [44] just reported MS-PVD plasma treatment of polypropylene surface utilizing sputtering of Ag, Cu and their oxides in order to impart antimicrobial activity [44].…”
Section: Deposition Of Antimicrobial Plasma Coatingsmentioning
confidence: 99%
“…An average value of the contact angle between the sample surfaces and a minimum of two drops was measured using the sessile drop method. The static contact angle was obtained analyzing the captured images using the Tangent Method 1 algorithm [11]. The wettability of the surface with a polar (H2O) and non-polar (diiodomethane) solvent was analyzed.…”
Section: Coatings Characterizationmentioning
confidence: 99%